Assessment of methods to estimate the level of service on third-class roads - Flores, Adriana (2024)
This study evaluates four methods to estimate the level of service for third-class highways through an Analytic Hierarchy Process (AHP) comparative matrix. The four methods are: i) Speed and Intensity Relation Method, ii) Highway Capacity Manual, iii) Invias Method, and iv) Percent Time-Following. A field inspection was performed to obtain highway data, such as the geometric characteristics of the road, vehicle volume, and vehicle speed. Considering this data and the corresponding methodologies of each method, the level of service of the highway is obtained. Results indicate a level of service of D in each method. The AHP comparative matrix is used to decide which method is the most adequate based on precision, time that takes to obtain the result (speed of response) and cost. Results indicate that the most appropriate method for estimating the level of service is the speed intensity relation method, mainly due to the low data required to estimate the LOS, making it a low-cost, and low-effort method to be conducted.